Recurrent cholangiocarcinoma with long-term survival by multimodal treatment: A case report - Sota, Yuki (Mol Clin Oncol, 2021)
Long-term outcomes after surgical resection of bile duct cancer remain unsatisfactory, and survival, particularly after tumor recurrence, is poor. Gemcitabine and cisplatin combination (GC) therapy is the standard first-line treatment; however, second-line approaches are yet to be established. Radiotherapy may prolong the survival of patients with advanced biliary tract cancer, and particle radiotherapy delivers a more concentrated dose than conventional radiotherapy to deeper tumors. The present report describes the long-term survival of a 65-year-old man with distal bile duct cancer of pathological stage IIA (T2N0M0; depth of invasion, 5.5 mm) following multimodal treatment. Following subtotal stomach-preserving pancreatoduodenectomy, multiple hepatic recurrences were identified 9 months later, and GC therapy was initiated. The tumors were no longer evident 18 months later, and GC therapy was discontinued at the patient's request. A computed tomography (CT) scan performed 30 months after surgery identified a new solitary hepatic recurrence and duke pancreatic monoclonal antigen type-2 (DUPAN-2) levels were increased. Further GC therapy was declined. Carbon ion radiotherapy (CIRT) at a dose of 60 Gy [relative biological effectiveness (RBE)-weighted absorbed dose] was then delivered in four fractions over 4 days [15 Gy (RBE)/day]. Tumor size decreased on CT, and fluorodeoxyglucose-positron emission tomography/CT revealed a decline in the standardized uptake value of the tumor after 2 months, with decreased DUPAN-2 levels. Following regrowth of the hepatic recurrence, CIRT was repeated at a dose of 66 Gy (RBE) in four fractions over 4 days [16.5 Gy (RBE)/day] and stable disease was maintained for 19 months. After 19 months, CT revealed tumor regrowth and another new metastatic lesion was identified in the left kidney. The patient received systematic chemotherapy again and died of the disease 81 months after the initial surgery. In conclusion, CIRT is a potential treatment option to control solitary recurrence of biliary tract cancer.